Convergent Validity for the Individual Music-Centered Assessment Profile for Neurodevelopmental Disorders. (21st February 2022) - Carpente, John A; Gattino, Gustavo Schulz; Berrones Cortez, Gisela X; Kelliher, Michael; Mulholland, Jill
Abstract: A significant percentage of music therapists actively provides services to children with autism spectrum disorder (ASD). There is an absence, however, of a widely accepted clinical instrument, specific to music therapy work with this population, that demonstrates psychometric validation. Establishing commonality in assessing and documenting this particular work within the field would be pivotal to furthering the efforts which have established music therapy as evidenced-based practice. A study was conducted to explore the convergent validity between the Musical Emotion Assessment Rating Scale (MEARS), which is Scale I of the Individual Music-Centered Assessment Profile of the Neurodevelopmental Disorders (IMCAP-ND) assessment tool, with the Social Affect Scale domains and item variables of the Autism Diagnostic Observation Schedule (ADOS). The data revealed statistical significance, thus supporting convergent validity with several specific MEARS scores when compared with the ADOS Social Affect domain score. The current investigation supports the IMCAP-ND's soundness as an assessment tool possessing valid and reliable psychometric properties. The convergent validity between MEARS and ADOS showed positive results in the area of social affect. Implications of this study are related to clinical practice and may impact how music therapists assess children with autism. Furthermore, this study contributes to the growing body of music therapy assessments that have yielded valid and reliable scores used to evaluate core features of ASD (e.g., social affect).